An economy and reliability co-optimization planning method of adiabatic compressed air energy storage for urban integrated energy system. (August 2021) - Yin, Binxin; Li, Yaowang; Miao, Shihong; Lin, Yujun; Zhao, Haipeng
Highlights: The previous reliability index is difficult to be quantified under the same unified framework with the economy index. Therefore, a new reliability index is proposed for reliability and economy co-optimization. With incorporating the economy and reliability indices into the optimization objects, the first economy and reliability co-optimization planning model of A-CAES for UIES is established. The planning scheme obtained by the economy and reliability co-optimization planning model is more reasonable, because it considered the significant effect of energy storage on the system reliability. Considering the solving efficiency of the optimal planning problem, the planning model is formulated based on a bi-level optimization model including the planning level optimization and scheduling level optimization. The constraints at the scheduling level of the optimal planning model can effectively reflect the operation of the UIES whether the devices in UIES are under normal or fault status. Abstract: The improving energy supply reliability requirements pose significant challenges to the energy storage planning in the urban integrated energy system (UIES). Traditional energy storage planning methods usually only take the economy optimization as the objective. These methods have difficulty meeting the requirement of reliability. The co-optimization of economy and reliability has been regarded as a new target. However, this new target is difficult to be achieved because of the complexity of energy storage resources in UIES and the nonlinearity of mathematical formulation to express the reliability. Therefore, how to achieve the maximum comprehensive improvement of economy and reliability within the limited scope of planning resources is a key issue that needs to be resolved. Adiabatic compressed air energy storage (A-CAES) has the capability of combined cooling, heating and power supply. The incorporation of A-CAES in UIES can improve the system economy and reliability effectively. To this end, a reasonable bi-level optimal planning method for A-CAES combined with heat/cold energy storage is proposed considering the economy and reliability co-optimization. Firstly, the mathematical formulations of economy and reliability objectives are presented separately. To unify the two planning objects, the reliability object is transformed from the minimum outage capacity into the minimum outage penalty cost, which is regarded as the reliability cost. The reliability cost and economy cost are integrated as the objective function of the planning level. Then, based on the rated power and capacity of A-CAES obtained from the planning level, the optimal scheduling model of UIES is established for evaluating the annual system operation cost and reliability cost. Finally, a UIES containing an A-CAES is used for simulation analysis. The simulation results show that the proposed model can achieve the comprehensive optimization of economy and reliability.